13C-metabolic flux analysis of lipid accumulation in the oleaginous fungus Mucor circinelloides. (December 2015) - Zhao, Lina; Zhang, Huaiyuan; Wang, Liping; Chen, Haiqin; Chen, Yong Q.; Chen, Wei; Song, Yuanda
Highlights: First report showing 13 C-metabolic flux analysis in Mucor circinelloides . Malic enzyme and ATP: citrate lyase played an important role in lipid accumulation. High lipid-producing strain showed higher flux in PPP and lower flux in TCA cycle. Abstract: The oleaginous fungus Mucor circinelloides is of industrial interest because it can produce high levels of polyunsaturated fatty acid γ-linolenic acid. M. circinelloides CBS 277.49 is able to accumulate less than 15% of cell dry weight as lipids, while M. circinelloides WJ11 can accumulate lipid up to 36%. In order to better understand the mechanisms behind the differential lipid accumulation in these two strains, tracer experiments with 13 C-glucose were performed with the growth of M. circinelloides and subsequent gas chromatography–mass spectrometric detection of 13 C-patterns in proteinogenic amino acids was carried out to identify the metabolic network topology and estimate intracellular fluxes. Our results showed that the high oleaginous strain WJ11 had higher flux of pentose phosphate pathway and malic enzyme, lower flux in tricarboxylic acid cycle, higher flux in glyoxylate cycle and ATP: citrate lyase, together, it might provide more NADPH and substrate acetyl-CoA for fatty acid synthesis.